The Effect of Price and Service Quality on Customer Satisfaction at J Bross Computer Padang - Hidayati, Habibatul; Dandi, Dandi (Bina Bangsa International Journal of Business and Management, 2023)
The research aimed to analyse the effect of price and quality service through the customer satisfaction at J Bross Computer Padang. The research used quantitative research, method with using accidential sampling by taking sample 96 respondents. The data analysis used in this research is the multiple regression analysis The result showed that the price and quality service have a positive and significant effect through the customer satisfaction